Self-reported symptoms and objective measures in idiopathic hypersomnia and hypersomnia associated with psychiatric disorders: a prospective cross-sectional study - Bušková, Jitka; Novák, Tomáš; Miletínová, Eva; Králová, Radana; Košt Álová, Jana; Kliková, Monika; Veldová, Karolina (Journal of clinical sleep medicine, 2022)
STUDY OBJECTIVES: In some patients, it is difficult to correctly nosologically classify daytime sleepiness. Clinical manifestations may be nonspecific; on the basis of objective measures it is possible to determine the current severity of sleepiness, but they do not always allow accurate diagnosis. It is especially difficult to distinguish between idiopathic hypersomnia (IH) and hypersomnia associated with a psychiatric disorder (PSY). METHODS: To find significant differences between the IH and PSY groups, we included 67 patients (IH, n = 15; PSY, n = 52) in the study, focusing on differences in self-reported symptoms, evaluating current depressive symptoms using the Beck Depression Inventory-II score and personality traits measured by the Temperament and Character Inventory. All of the patients underwent polysomnography, the Multiple Sleep Latency Test, and ad libitum sleep monitoring. RESULTS: The patients with IH showed greater difficulty than those in the PSY group with waking up in the morning (P < .001) and complained of memory (P = .04) and attention deficit (P = .006). They also showed higher total sleep time (P < .001) and sleep efficiency (P = .007) and a shorter mean sleep latency on the Multiple Sleep Latency Test (P < .001). Nevertheless, the IH and PSY groups did not differ in Beck Depression Inventory scores or personality characteristics. CONCLUSIONS: IH is a syndrome in which depression/external life stressors and personality characteristics also play a role. Patients with IH may benefit from the cooperation of sleep specialists with psychotherapists/psychiatrists. CITATION: Bušková J, Novák T, Miletínová E, et al. Self-reported symptoms and objective measures in idiopathic hypersomnia and hypersomnia associated with psychiatric disorders: a prospective cross-sectional study. J Clin Sleep Med. 2022;18(3):713-720.
Keywords: narkolepsie; Cross-Sectional Studies; Mental Disorders; Narcolepsy; prospektivní studie; zpráva o sobě; průřezové studie; Prospective Studies; lidé; Disorders of Excessive Somnolence; Humans; Idiopathic Hypersomnia; poruchy nadměrné spavosti; idiopatická hypersomnie; duševní poruchy; Self Report